Effect of rumen-protected choline supplementation on production performance and haemato-biochemical profile of Kankrej cows - Pawar, Mahesh M; Patil, Shrikant S; Panchasara, Harshad H; Patel, Jayveer R; Ahuja, Love C; Raut, Akash S; Modi, Chetna P; Gupta, Jay Prakash (Indian Journal of Dairy Science, 2023)
The peripartum period is critical for productivity, reproduction and health of dairy cows due to higher demands for nutrients and lower feed intake. A study was conducted to examine the effect of supplementation of rumen-protected choline chloride (RPC) on production performance and haemato-biochemical parameters of Kankrej cows. Twenty Kankrej cows were randomly allocated to two treatment groups: control (CON: fed basal diet without supplement) and treatment (RPC: basal diet supplemented with 50 g/d/cow of RPC) from 4-weeks pre-partum through 8-weeks post-partum. Results showed that average body weights and dry matter intake were not affected (P<0.05) by the supplementation of RPC. There was significant (P<0.05) improvement in yields of milk (11.10 vs. 12.45 kg/d), FCM (10.93 vs. 12.49 kg/d) and ECM (12.07 vs. 13.76 kg/d) with RPC supplementation when compared with cows fed on the control diet. The milk fat, SNF, total solids, protein and lactose contents did not differ (P>0.05) between the treatment groups. Supplementation of RPC improved feed efficiency in terms of kg of 4% FCM/kg of DMI and kg of ECM/kg of DMI in lactating cows. The higher (P<0.05) serum glucose concentration (65.72 vs.62.05 mg/dL) was observed in RPC than the CON. Supplementation of RPC reduced (P<0.05) concentration of serum triglycerides (27.27 vs. 31.38 mg/dL) as compared to the CON group. Other estimated blood metabolites were not influenced (P>0.05) by the supplementation of RPC. In conclusion, supplementation of 50 g/d rumen-protected choline during peripartum period improved milk production, feed efficiency and blood glucose in Kankrej cows.